Identification of the early cretaceous granitic pluton and tectonic implications in the middle gangdese belt, southern tibet - Wang, Qingling; Meng, Yuanku; Wei, Youqing; Jiang, Li; Wang, Zhenzhen; Mao, Guangzhou (Frontiers in Earth Science, 2022)
The Gangdese magmatic belt of southern Tibet is an ideal place to study Neo-Tethyan subduction, continental crustal growth and reworking. However, there are still controversies with regard to the evolution of the Neo-Tethys Ocean, the magma source and the detailed diagenetic processes of igneous rocks in the Gangdese belt. The Early Cretaceous magmatic exposures are sporadic in the Gangdese magmatic belt. Thus the finding of the new exposure is key to understanding the scenarios of the Neo-Tethys Ocean and geological background of southern Tibet during the Early Cretaceous. In this contribution, we undertook systematic geochronology, whole-rock geochemistry and zircon Lu-Hf isotopic studies on a newly identified granitic pluton in the middle Gangdese belt (Quesang area), southern Tibet. The results show that zircon U-Pb dating of three representative samples yielded a weighted age of 120 ± 1.4 Ma, 117.3 ± 2.5 Ma and 114.0 ± 1.3 Ma, respectively, which indicate the emplacement and crystallization age belonging to the Aptian stage of the Early Cretaceous in response to the northward subduction of the Neo-Tethyan oceanic lithosphere beneath the Lhasa terrane. In situ zircon Lu-Hf isotopic analyses indicate that ƐHf(t) values of the studied granitic pluton are predominantly positive ranging from 7.2 to 11.4, and one zircon shows negative ƐHf(t) value (−6.26), implying that a small amount of ancient continental crustal materials might have participated in the magma evolution. Geochemically, the granite samples are enriched in large ion lithophile elements (LILE) and light rare earth elements (LREE), but depleted in heavy rare earth elements (HREE), indicating arc-type geochemical characteristics or subduction-related tectonic setting. In addition, combined with mineral assemblages, zircon Lu-Hf isotopic features and low molar Al2O3/(CaO+Na2O+K2O) (A/CNK) ratios of 0.91–1.10, the studied samples show a close affinity with I-type granites. Moreover, zircon oxygen fugacity results show that Ce4+/Ce3+ values range from 185 to 12, with a mean value of 78, indicating a low oxygen fugacity setting similar to the Chile ore-barren granitic plutons. In combination with published data, we argue that the Gangdese magmatic belt may have developed continuous magmatism (145–105 Ma), and the notion of magmatic lull might deserve more consideration during the Early Cretaceous. In this study, the Early Cretaceous granitic pluton might be the result of the northward subduction of Neo-Tethys oceanic lithosphere beneath the Lhasa terrane at a normal angle.